Meningkatkan Keterampilan dan Kreatifitas Santri Melalui Pengolahan Limbah Botol Plastik Menjadi Produk Siap Pakai - Rosalinda Wiemar; Cama Juli Rianingrum; Susy Irma Adisurya (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
Along with the development of technology and the needs of society, the production of packaged food and beverages is growing rapidly. Various materials are used as containers, mostly plastic, especially as drink containers. Besides being relatively cheap, lightweight, hygienic, it is also easy to process into an aesthetic and functional form. Unfortunately, this material is very difficult to decompose, so it has the potential to become waste that damages the environment and disturbs the view. Students at Islamic boarding schools are the next generation of the nation. Apart from primarily studying religious knowledge, they are also responsible for protecting and saving the environment. With self-financing, Raudhatul Ishlah Islamic Boarding School has limited funds to carry out daily student activities. For this reason, training that provides additional skills will be very beneficial for the students. The training method begins with a basic lecture on colors, design principles, an overview of the work to be made and tries to develop the creativity of the students by utilizing plastic bottle waste combined with natural materials around the pesantren. From this training, students get additional useful knowledge and skills so that they are more creative and productive. so that it can help students fill their spare time with positive activities and produce products according to the needs of students in Islamic boarding schools